Focal adhesion kinase as a new player in the biology of onco-hematological diseases: the starting evidence - Capasso, Guido; Mouawad, Nayla; Castronuovo, Maria; Ruggeri, Edoardo; Visentin, Andrea; Trentin, Livio; Frezzato, Federica (Frontiers in Oncology, 2024)
Focal adhesion kinase (FAK) is a non-receptor tyrosine kinase mainly found in the focal adhesion regions of the plasma membrane and it has a crucial role in migration and the remodeling of cellular morphology. FAK is also linked to several aspects of cancer biology, from cytokine production to angiogenesis, drug resistance, invasion, and metastasis, as well as epithelial-to-mesenchymal transition. The gene locus of FAK is frequently amplified in several human tumors, thus causing FAK overexpression in several cancers. Furthermore, FAK can influence extracellular matrix production and exosome secretion through cancer-associated fibroblasts, thus it has an important role in tumor microenvironment regulation. Although the role of FAK in solid tumors is well known, its importance in onco-hematological diseases remains poorly explored. This review collects studies related to FAK significance in onco-hematological diseases and their microenvironments. Overall, the importance of FAK in blood tumors is increasingly evident, but further research is required to confirm it as a new therapeutic target in hematological contexts.